Differential modification of genetic susceptibility to childhood eczema by two probiotics. Issue 10 (October 2014) - Morgan, A. R.; Han, D. Y.; Wickens, K.; Barthow, C.; Mitchell, E. A.; Stanley, T. V.; Dekker, J.; Crane, J.; Ferguson, L. R.
Summary Background In a double‐blind, randomized, placebo‐controlled birth cohort, we have recently shown a beneficial effect of Lactobacillus rhamnosus HN001 (HN001) for the prevention of eczema in children through to 6 years of age but no effect of Bifidobacterium animalis subsp lactis HN019 (HN019). Objective Among this cohort of children, we aim to investigate whether these probiotics could modify the expression of genetic predisposition to eczema conferred by genetic variation in susceptibility genes. Methods Thirty‐three eczema susceptibility SNPs (in eleven genes) were genotyped in 331 children of European ancestry. Results Children who carried a genetic variant that put them at a high risk of developing eczema were less likely to develop eczema if they had been randomized to the HN001 intervention group compared to those in the placebo group. HN019 was also able to protect against the effects of some SNPs. As well as modifying genetic susceptibility to childhood eczema, HN001 was also found to modify genetic susceptibility to eczema severity and atopy risk. Conclusion and Clinical Relevance This is the first study to show an effect of a probiotic on reducing eczema risk amongst those with particular eczema‐associated genotypes. Our findings suggest that Lactobacillus rhamnosus HN001 may be particularly effective in preventing eczema in children with specific high‐risk genotypes.